Community‐wide changes in intertaxonomic temporal co‐occurrence resulting from phenological shifts. (29th February 2016) - Hua, Fangyuan; Hu, Junhua; Liu, Yang; Giam, Xingli; Lee, Tien Ming; Luo, Hao; Wu, Jia; Liang, Qiaoyi; Zhao, Jian; Long, Xiaoyan; Pang, Hong; Wang, Biao; et al.
Abstract: Global climate change is known to affect the assembly of ecological communities by altering species' spatial distribution patterns, but little is known about how climate change may affect community assembly by changing species' temporal co‐occurrence patterns, which is highly likely given the widely observed phenological shifts associated with climate change. Here, we analyzed a 29‐year phenological data set comprising community‐level information on the timing and span of temporal occurrence in 11 seasonally occurring animal taxon groups from 329 local meteorological observatories across China. We show that widespread shifts in phenology have resulted in community‐wide changes in the temporal overlap between taxa that are dominated by extensions, and that these changes are largely due to taxa's altered span of temporal occurrence rather than the degree of synchrony in phenological shifts. Importantly, our findings also suggest that climate change may have led to less phenological mismatch than generally presumed, and that the context under which to discuss the ecological consequences of phenological shifts should be expanded beyond asynchronous shifts.